QUO VADIS’ NEW TESTAMENT STUDIES? - Lategan, Bernard C. (Scriptura, 2009)
The present reflection on the state of New Testament scholarship takes place against the background of a strong resurgence of religion on a global scale. This does not imply that New Testament studies can continue as usual. A critical re-examination is needed to ensure that the discipline continues to play a meaningful role in the future. Rather than undertaking a comprehensive review, certain distinctive topics are highlighted: the importance of the original languages, the alternative as point of departure, a historical consciousness, an inclusive approach and an ethics of the deed. The article is concluded with some suggestions for restructuring the curriculum of theological training and for deepening the concept of human dignity.